2019
DOI: 10.1007/978-3-030-28014-7_7
|View full text |Cite
|
Sign up to set email alerts
|

Participatory Research on Heritage- and Culture-Based Development: A Perspective from South-East Europe

Abstract: The objective of the chapter is to highlight the relevance and implementation of culture-and heritage-led regional and local development in SouthEast Europe. By implementing the participatory research methodology at two major events in Europe, we analysed the practitioners' views on the topics of culture-and heritage-led development. Our results showed that culture and heritage are characteristic and unique and could provide a distinctive added value for regional development as a branding tool, a factor of mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The deeper insights into participants' experiences, opinions, thoughts, and recommendations not only benefited the researchers in generating more detailed data. Through participation in focus groups, community members reported benefits including new insights and a broader perspective on issues shared within the group, in addition to a sense of inclusion and community building ( 44 ). This was most evident in the study by Ybarra et al ( 41 ), which found that online focus groups discussions should be further explored as low-cost prevention programs.…”
Section: Discussionmentioning
confidence: 99%
“…The deeper insights into participants' experiences, opinions, thoughts, and recommendations not only benefited the researchers in generating more detailed data. Through participation in focus groups, community members reported benefits including new insights and a broader perspective on issues shared within the group, in addition to a sense of inclusion and community building ( 44 ). This was most evident in the study by Ybarra et al ( 41 ), which found that online focus groups discussions should be further explored as low-cost prevention programs.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, however, there is the question of whether locals should be allowed to change their houses as they wish, or if there should be strict regulations in place to restrict such changes in order to preserve the characteristics of the area. This is not a new question as other researchers have raised it before when discussing authenticity and its challenges (Cole, 2007), with some arguing that hosts should have the right to decide on the matter (Zhou et al, 2018) and others proposing context-specific solutions (Bamert et al, 2016;Nared & Bole, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The present study responds to this call by investigating the challenges faced by an important heritage destination in Eastern Europe, a region rich in cultural heritage that has been little researched (Nared & Bole, 2020). This part of Europe presents specific characteristics due to its communist past and the transition process that these countries have been going through over the past decades (South East European Heritage, 2011).…”
Section: Heritage Tourism and World Heritage Sitesmentioning
confidence: 99%
“…In its contemporary meaning, it is made up of a tangible or physical component, the tangible cultural heritage; and an intangible component, the non-material cultural heritage [9]- [11]. The valuation of CH has been imposed in the narrative that guides the design of tourism products, due to the great dynamizing potential of the society and economy of the territories where it is promoted [12]. On the other hand, it has favored the development of cultural heritage tourism, as a tourism with a global dimension [13].…”
mentioning
confidence: 99%